Sulfur nanoparticle-coated urea improves growth and nitrogen use efficiency in wheat (Triticum aestivum L.) and rice (Oryza sativa L.) - Faraz, Ahmad; Imran, Asma; Raza, Hammad; Iqbal, Muhammad; Rehman, Asma (Frontiers in Nanotechnology, 2025)
Nitrogen (N) is an essential macronutrient required for plant productivity. Urea is a major source of N in global agriculture systems that is lost due to leaching, runoff, and volatilization, inflicting serious productivity, economic, and environmental issues. In contrast, coated urea minimizes N losses by decreasing urease activity and enhances its efficiency by maintaining a continuous N supply for plant uptake and productivity. The present study describes the impact of sulfur nanoparticle (SNP)-coated urea (SNPCU) on the morpho-physiological, biochemical, and yield traits of rice and wheat. Chemically synthesized SNP coated onto urea revealed a fine layer of SNP on urea under a scanning electron microscope. Two varieties each of rice and wheat grown in pots were fertilized as follows: control N/recommended non-coated urea U100, three doses of SNPCU (50%, 70%, and 90% of recommended N) in split doses (40% at transplanting, 30% at tillering, and 30% at the panicle stage). Analysis revealed that SNPCU at all doses increased the growth and yield parameters of both crops. The maximum increase was observed in SNPCU90, that is, chlorophyll (up to 39%), carotenoids and proteins (up to 20%), sugars and amino acids (up to 60%), along with an increase of at least 5% or more in agronomic efficiency, 10% or more in grain weight, 6% or more in harvest index, and 70% or more in N uptake in both cultivars of wheat and rice. SNPCU90 increased the nitrogen recovery efficiency by 34% and 26% in wheat varieties Galaxy and FSD-2008, while 36% and 30% in Green Super Rice and 1121 Basmati rice, respectively. SNPCU90 decreased urease activity up to 37%, 52% on day 2, and 16% and 25% on day 15 in wheat and rice, respectively. This delay increased the duration of N availability in soil for wheat and rice plants, resulting in increased nitrogen use efficiency (NUE) till 15 days. This study has demonstrated that SNPCU minimizes N loss, revealing that even a lower application of SNPCU fulfills the crop N demand. It is concluded that SNPCU at lower rates can be used for large-scale testing in fields for reducing N losses and improving yields.